Application of Linear Probability Model to Road Traffic Crash - Ogunmola, Adeniyi Oyewole; Ogebe, Victor Ajibo; Onowuzou, James Oruarooghene (Darul Yasin Al Sys, 2025)
Road traffic crashes remain a critical public health and safety concern, particularly in developing countries such as Nigeria, where they constitute one of the leading causes of mortality and injury. This study investigates the likelihood that a road traffic crash in each of Nigeria’s six geopolitical zones and in the country as a whole results in a minor incident. Quarterly data on road traffic crashes were sourced from the official database of the Federal Road Safety Corps and analyzed using a linear probability model. The model estimates the probability of a crash being categorized as minor across regions. Findings indicate that the probability of minor road traffic crashes is consistently below 20 percent in all zones and nationally, suggesting that the majority of reported crashes result in major damage or casualties. These results point to a concerning trend in crash severity across Nigeria. The study highlights the urgent need for enhanced traffic safety interventions, stricter enforcement of road regulations, improved vehicle and infrastructure standards, and more effective emergency response systems. Emphasizing preventative strategies and public awareness campaigns could help shift the balance toward more minor, less harmful outcomes when crashes do occur. Ultimately, the goal should be to ensure that in the event of a road traffic crash, the incident remains minor in nature, minimizing harm to life and property.